Identification of key genes and biological regulatory mechanisms in diabetic nephropathy: Meta-analysis of gene expression datasets - Fatemeh Hojjati; Amir Roointan; Alieh Gholaminejad; Yasin Eshraghi; Yousof Gheisari (Nefrología (English Edition), 2023)
Background: Diabetic nephropathy (DN) which refers to the cases with biopsy proven kidney lesions, is one of the main complications of diabetes all around the world; however, the underlying biological changes causing DN remain to be understood. Studying the alterations in gene expression profiles could give a holistic view of the molecular pathogenicity of DN and aid to discover key molecules as potential therapeutic targets. Here, we performed a meta-analysis study that included microarray gene expression profiles coming from glomerular samples of DN patients in order to acquire a list of consensus Differentially Expressed Genes (meta-DEGs) correlated with DN. Methods: After quality control and normalization steps, five gene expression datasets (GES1009, GSE30528, GSE47183, GSE104948, and GSE93804) were entered into the meta-analysis. The meta-analysis was performed by random effect size method and the meta-DEGs were put through network analysis and different pathway enrichment analyses steps. MiRTarBase and TRRUST databases were utilized to predict the meta-DEGs related miRNAs and transcription factors. A co-regulatory network including DEGs, transcription factors and miRNAs was constructed by Cytoscape, and top molecules were identified based on centrality scores in the network. Results: The identified meta-DEGs were 1364 DEGs including 665 downregulated and 669 upregulated DEGs. The results of pathway enrichment analysis showed, “immune system”, “extracellular matrix organization”, “hemostasis”, “signal transduction”, and “platelet activation” to be the top enriched terms with involvement of the meta-DEGs. After construction of the multilayer regulatory network, several top DEGs (TP53, MYC, BTG2, VEGFA, PTEN, etc.), as well as top miRNAs (miR-335, miR-16, miR-17, miR-20a, and miR-93), and transcription factors (SP1, STAT3, NF-KB1, RELA, E2F1), were introduced as potential therapeutic targets in DN. Among the regulatory molecules, miR-335-5p and SP1 were the most interactive miRNA and transcription factor molecules with the highest degree scores in the constructed network. Conclusion: By performing a meta-analysis of available DN-related transcriptomics datasets, we reached a consensus list of DEGs for this complicated disorder. Further enrichment and network analyses steps revealed the involved pathways in the DN pathogenesis and marked the most potential therapeutic targets in this disease. Resumen: Antecedentes: La nefropatía diabética (ND), que se refiere a los casos con lesiones renales comprobadas por biopsia, es una de las principales complicaciones de la diabetes en todo el mundo. Sin embargo, los cambios biológicos subyacentes que causan la ND aún no se han entendido. Aquí realizamos un estudio de metaanálisis que incluyó perfiles de expresión génica de micromatrices provenientes de muestras glomerulares de pacientes con ND para adquirir una lista de genes expresados diferencialmente (meta-DEG) de consenso correlacionados con ND. Métodos: Después de los pasos de control de calidad y normalización, se ingresaron en el metaanálisis cinco conjuntos de datos de expresión génica (GES1009, GSE30528, GSE47183, GSE104948 y GSE93804). El metaanálisis se realizó mediante el método de tamaño de efecto aleatorio y los meta-DEG se sometieron a análisis de red y a diferentes pasos de análisis de enriquecimiento de ruta. Se utilizaron las bases de datos MiRTarBase y TRRUST para predecir los factores de transcripción y los miARN relacionados con los meta-DEG. Cytoscape construyó una red de corregulación que incluye DEG, factores de transcripción y miARN, y las moléculas principales se identificaron en función de las puntuaciones de centralidad en la red. Resultados: Los meta-DEG identificados fueron 1.364 DEG, incluidos 665 DEG regulados negativamente y 669 regulados positivamente. Los resultados del análisis de enriquecimiento de vías mostraron que «sistema inmunitario», «organización de la matriz extracelular», «hemostasia», «transducción de señales» y «activación de plaquetas» son los términos más enriquecidos con la participación de los meta-DEG. Después de la construcción de la red reguladora multicapa, varios DEG principales (TP53, MYC, BTG2, VEGFA, PTEN, etc.), así como miARN principales (miR-335, miR-16, miR-17, miR-20a y miR -93) y factores de transcripción (SP1, STAT3, NF-KB1, RELA, E2F1) se introdujeron como posibles dianas terapéuticas en la ND. Entre las moléculas reguladoras, miR-335-5p y SP1 fueron las moléculas de factor de transcripción y miARN más interactivas con las puntuaciones de grado más altas en la red construida. Conclusión: Al realizar un metaanálisis de los conjuntos de datos transcriptómicos relacionados con ND disponibles, llegamos a una lista de consenso de DEG para este trastorno complicado. Los pasos posteriores de enriquecimiento y análisis de redes revelaron las vías involucradas en la patogénesis de la ND y marcaron los objetivos terapéuticos más potenciales en esta enfermedad.